The Influence of the Montessori Method on Early Childhood Development - Anggun, Setiani; Jimi, Harianto; Tri, Dewanti; Herpratiwi, Herpratiwi (CV. Creative Tugu Pena, 2024)
This research aims to determine the Montessori method's influence on early childhood literacy development. The main problem in this research is whether the Montessori method influences students' reading, writing, and arithmetic abilities in the Bdi PAUD KB Permata Hati Way Kanan group. The aim to be achieved in this research is to find out how much influence the Montessori method has on the Calistung abilities of group B students at PAUD KB Permata Hati Way Kanan. This type of research isPre-Experimental. The experimental design that will be used is the One Group Pretest-Posttest Design. This design exists as a pretest before being treated and a posttest after being given treatment. Data collection techniques include observation, documentation, and tests. The subjects in this research were 15 students from the Bdi PAUD KB Permata Hati Way Kanan group. The research results showed that after being given the Montessori method treatment, the Calistung abilities of group B students at PAUD KB Permata Hati Way Kanan increased. This is based on results post-test with a high percentage of the assessment of developing according to expectations (BSH. The use of the Montessori method affects the Calistung ability of group B students at PAUD KB Permata Hati Way Kanan, as evidenced by the average difference of 25% for pretest results and 36% for posttest results. There is a difference between using the Montessori method and the Montessori method before using the Montessori method on the Calistung ability of group B students at PAUD KB Permata Hati Way Kanan. The Wilcoxon test proves that the calculated Z value is 3.4 and the Z table is 1.635 Z table (1.635). Based on the results of this research, the Montessori method influences the Calistung ability of group B students at PAUD KB Permata Hati Way Kanan. Keywords: Montessori Method, Elementary School, Childhood Literacy Development